Knowledge and attitudes of male nursing students concerning male breast cancer and ways of prevention - Ateya Megahed Ibrahim; Donia Elsaid Fathi Zaghamir; Mohamed Gamal Elsehrawey; Mohamed A. El-Sakhawy (Elsevier, 2024)
Background: Male breast cancer remains largely unfamiliar to students, the general public, and healthcare professionals. In stark contrast, female breast cancer, being more prevalent, has garnered significant awareness across various demographics. Objective: This study aimed to assess knowledge and attitudes of male nursing students about male breast cancer and prevention measures. Methods: A descriptive research design was employed for this study. The participant pool comprised 165 male nursing students enrolled in the nursing program at the College of Nursing, Prince Sattam Bin Abdulaziz University. Data collection involved utilizing a participant identification form and a questionnaire, encompassing three primary sections addressing sociodemographic data, knowledge, and attitudes of the participants regarding male breast cancer and ways of prevention. Results: The study revealed that the total mean score for knowledge among the participants regarding male breast cancer was 19.03±4.414. Additionally, the total mean score for their attitudes toward male breast cancer was 29.8±6.041. The analysis indicated a highly statistically significant association between the total knowledge scores and total attitude scores of the participants (P < 0.05). Furthermore, there was a notable and statistically significant relationship between the educational level of the participants and their total attitude scores. Conclusion: Male nursing students lacked understanding about male breast cancer and had a poor attitude toward it. Recommendation: These results provide a starting point for the creation of evidence-based, gender-specific health promotion and disease prevention strategies for men, while more research with bigger samples is required. Also, this study makes a significant contribution to the creation of an effective program meant to increase high nursing students' awareness of breast cancer and strategies to support their loved ones in the prevention and treatment of the disease.